Monetary Transmission on Company Value of Bank Syariah Indonesia - Pratiwi, Palupi; Risyantika, Dewi; Fuadi, Fatih; Iqbal, Muhammad (Al-Mashrof: Islamic Banking and Finance, 2025)
The study investigates how inflation, money supply, and the BI Rate influence the firm value of Bank Syariah Indonesia (BSI) after its 2021 consolidation. This study aims to examine the effect of key monetary policy variables inflation, money supply and BI Rate on the firm value of BSI. Using a quantitative approach, quarterly secondary data from 2021–2024 were collected from Bank Indonesia, Statistics Indonesia, and BSI financial reports and analyzed through multiple linear regression. The results reveal that inflation and the BI Rate significantly and negatively affect firm value, while the money supply shows no significant effect. These findings indicate that monetary tightening diminishes investor valuation of BSI, whereas liquidity expansion does not necessarily translate into higher market value. The study contributes to theory by showing that Islamic banks remain sensitive to conventional monetary policy transmission and offers insights for risk management and Islamic finance development. Keywords: Bank Syariah Indonesia, BI Rate, Inflation, Monetary Policy, Money Supply